Pengaruh teknik dan waktu pencampuran pada pembuatan lembaran cocodust berkaret untuk bahan peredam suara - Arum Yuniari (Majalah Kulit, Karet, dan Plastik, 2009)
Research about cocodust rubber sheet production for sounds absorbent material was determined to improve mixing technology between cocodust and latex compound so there can be gained effective mixing technology. There are 2 methods regarding to mixing technology which were A method and B method with time variation method between 2, 3 until 4 minute respectively time. A method was cocodust with sieved by 50 mesh siefter mixed with water (ratio time between cocodust and water 1:3) and subsequently cocodust was mixed with latex compound. While B method was mixing latex compound and water (the mixture consisting of 3 part of water and 1 part of latex) and the final product was blended. The result show that A method with time variation of 2 – 3 minutes was the best effective mixing method. The result of a method can be easily implemented, having homogeny compound and good product performance, which was characterized by mass density 0,40 g/cm3, water content 7,29 – 7,57%, flexibility strength 2,87 – 4,05 kg/cm2, vertical tensile strength 1,97 – 3,12 kg/cm2, ability to be nailed 4,95 – 5,92 kg, thickness grows 7,5 – 8,28% and sound absorption coefficient at the frequency 500 Hz was 0,70.